Responding to a Mumps Outbreak Impacting Immigrants and Low–English-Proficiency Populations. Issue 2 (March 2020) - Koeller, Sarah; Meyer, Diane; Shearer, Matthew P.; Hosangadi, Divya; Snyder, Michael; Nuzzo, Jennifer B.
Abstract : Objectives: To examine outbreak response–associated costs, lessons learned, and challenges encountered during a local health department's response to a mumps outbreak. Design: We conducted semistructured interviews with individuals directly involved in the response to a mumps outbreak and analyzed outbreak response–associated cost data. Setting: In March-July 2018, a mumps outbreak occurred in Chester County, Pennsylvania. The outbreak primarily affected an immigrant community, some of whom spoke little or no English and were uninsured and/or undocumented. This necessitated an urgent response from the Chester County Health Department, which implemented a variety of public health interventions, including outreach to local health care providers and the execution of vaccination clinics at 2 local mushroom farms where case contacts worked. A total of 39 suspected or confirmed mumps cases were reported in Chester County, and 22 suspected or confirmed cases were reported by 2 neighboring jurisdictions. Participants: Health department employees (n = 7) and community partners (n = 2). Areas of expertise included emergency preparedness, nursing, medicine, disease surveillance, and epidemiology. Main Outcome Measure: Operational challenges encountered and lessons learned during the mumps outbreak response, including outbreak response–associated costs, which could inform other communities' planning and preparedness for outbreaks in similar populations and improve outbreak response operations. Results: Immigration status emerged as a key challenge, which highlighted the importance of building trust through community outreach and partnerships and the need for culturally competent communication. In addition, vaccine availability, accessibility, and cost played a major role in response operations and necessitated the involvement of community partners to mitigate these barriers. Outbreak response–associated costs totaled 35 305. Conclusions: The challenges that occurred in this outbreak are broadly relevant to outbreaks that affect similar immigrant communities. Health departments that serve such populations can utilize these lessons to develop improved outbreak response plans that account for these challenges. Abstract : Supplemental Digital Content is Available in the Text.